Antifungal and Antibiofilm Activity of Cyclic Temporin L Peptide Analogues against Albicans and Non-Albicans Candida Species - Rosa Bellavita; Angela Maione; Francesco Merlino; Antonietta Siciliano; Principia Dardano; Luca De Stefano; Stefania Galdiero; Emilia Galdiero; Paolo Grieco; Annarita Falanga (MDPI AG, 2022)
Temporins are one of the largest families of antimicrobial peptides with both anti-inflammatory and antimicrobial activity. Herein, for a panel of cyclic temporin L isoform analogues, the antifungal and antibiofilm activities were determined against representative Candida strains, including C. albicans, C. glabrata, C. auris, C. parapsilosis and C. tropicalis. The outcomes indicated a significant anti-candida activity against planktonic and biofilm growth for four peptides (3, 7, 15 and 16). The absence of toxicity up to high concentrations and survival after infection were assessed in vivo by using Galleria mellonella larvae, and the correlation between conformation and cytotoxicity was investigated by fluorescence assays and circular dichroism (CD). By combining fluorescence spectroscopy, CD, dynamic light scattering, confocal and atomic force microscopy, the mode of action of four analogues was hypothesized. The results pinpointed that peptide 3 emerged as a non-toxic compound showing a potent antibiofilm activity and represents a promising compound for biomedical applications.